CiNAC2 positively regulates drought stress tolerance by promoting superoxide dismutase activity in pecan (Carya illinoinensis) - Bingbing Yang; Chaochen Yang; Juanjuan Chen; Huadong Ren; Kailiang Wang; Linxiu Liu; Xiaohua Yao (Horticultural Plant Journal)
Pecan is an extremely important crop cultivated worldwide for edible nuts and nut oil. Considering the changes in precipitation and soil moisture caused by climate change and worsening global water scarcity, it is important to understand the mechanism of pecan response to drought. To this end, this study investigated the response of pecan to drought stress and rehydration using physiological and transcriptomic analyses. Superoxide dismutase (SOD) enzyme activity in leaves was significantly upregulated during drought stress, suggesting that it might play an important role in drought response. Weighted gene co-expression network analysis of the transcriptome data was used to screen for a key drought-responsive gene, CiNAC2, which was overexpressed in Arabidopsis thaliana for functional validation. The analysis of stomatal apertures and the water loss rate in leaves showed that CiNAC2 might respond to drought stress via mediating stomatal aperture size. In addition, CiNAC2 could promote root growth under drought conditions. CiSOD1 was verified as a direct target gene of CiNAC2 by yeast one-hybrid assay dual-luciferase reporter assay. Yeast one-hybrid analysis confirmed that CiNAC2 bound to the promoters of CiSOD1. Transient expression in Nicotiana benthamiana epidermis showed that CiNAC2 upregulated the expression of CiSOD1. These results demonstrated that CiNAC2 enhanced drought stress tolerance via promoting SOD activity in pecan and provided a theoretical basis for breeding drought-resistant varieties in pecan.